General and Alcohol-Related Social Media Use and Mental Health: a Large-Sample Longitudinal Study - Eilin K. Erevik; Ståle Pallesen; Øystein Vedaa; Cecilie S. Andreassen; Amandeep Dhir; Torbjørn Torsheim (Springer, 2022)
The current study aimed to investigate if general and alcohol-related social media use predicts symptoms of depression and anxiety. Students in Bergen, Norway, participated in a Web-based survey during fall 2015 (T1) and a follow-up survey during fall 2016 (T2). A total of 5217 participated in both surveys. Crude and adjusted linear regression analyses were conducted to investigate if social media use at T1 predicted depression and anxiety at T2. Several social media use variables (e.g., using Instagram) were positively associated with depression and anxiety over time, but these associations became non-significant when covariates were controlled for. Number of online friends was inversely related to depression whereas using Twitter was positively related to anxiety at T2, when covariates were controlled for. The effect sizes of the observed associations were all very small. The current study found little support for a relationship between social media use and mental health.